Curiosity Matematis Mahasiswa dalam Pembelajaran Daring Ditinjau Berdasarkan Level Kemampuan Akademik dan Gender (Studi Kasus dalam Pembelajaran Kalkulus Integral) - Zetriuslita Zetriuslita; Rezi Ariawan (Mathematics Education Study Program, 2021)
The possession of mathematical curiosity (curiosity) in learning Integral calculus is very important. Moreover, learning is carried out online due to the covid-19 pandemic. The level of academic ability and gender, which is a social behavior inherent in individuals, will indirectly contribute to mathematical curiosity (curiosity). Therefore, this study was conducted with the aim of describing students' mathematical curiosity in online learning in terms of academic ability level and gender. The Mathematics Education Study Program FKIP UIR is the place where this research is carried out. The implementation time is the odd semester of the 2020/2021 academic year with a sample of 50 people obtained with consideration. This research was conducted using quantitative research. The research instrument was a mathematical curiosity questionnaire which was given to students on a non-test basis with the help of google classroom. Descriptive analysis was used to analyze the data obtained in this study. The results of the analysis of research data inform that Overall, students' curiosity in bold learning is included in the criteria with a percentage of 78.88%. The mathematical Curiosity of students with a high level of academic ability is included in the criteria with a percentage of 79.79%, 78.19%, and the mathematical Curiosity of students with a low level of academic ability is included in the very strong criteria with a percentage of 83, 13% . The mathematical curiosity of male and female students is included in the criteria with a percentage of 75.89% and 78.74%